Main Street : How a City's Heart Connects Us All - Fullilove, Mindy Thompson, 1950- (Book collections on Project MUSE., 2020)
"How do Main Streets contribute to our mental health? This question took social psychiatrist Mindy Thompson Fullilove on an 11-year search through 178 cities in 14 countries. From informal observations, Fullilove discerns the larger architecture of Main Streets. She describes the myriad ways that Main Streets are shaped for social interactions and how they are a marker for the integrity of civilization. Her illustrated book shows how urban centers are essential for gathering people to share information and to tend civic and commercial tasks that benefit all. She addresses ways cities can cure, not only ills of an inequitable, post-industrial culture, but malaise of a post-pandemic culture seeking reconnection"--